Pengaruh Pengembangan Sumber Daya Manusia (SDM) Terhadap Kinerja Karyawan Pada Perusahaan Bido Collection - Ahmad Iqbal Nugraha (Lokawati : Jurnal Penelitian Manajemen dan Inovasi Riset, 2023)
The research is motivated by a problem where employee performance has decreased compared to the previous year, this indicates that employee performance is still not optimal. Human resource development carried out by the company has not had an impact on improving company performance. So the purpose of this research is to know and describe the development of human resources (HR) in the Bido Collection Company. Employee performance at the Bido Collection Company. The influence of human resource development (HR) on employee performance in the Company. The method used is descriptive quantitative. The research results show that . The development of human resources at the Bido Collection Company based on the responses of respondents is included in the very good category. This means that the Bido Collection Company has developed very well. The performance of the Bido Collection Company's employees is in the very good category. Artonya employees have a very good assessment during their work. This means that the performance appraisal of Bido Collection employees is very good and human resource development has a positive and significant effect on the performance of Bido Collection Company employees. This means that if the HR development of the Bido Collection company increases, it will be followed by an increase in the performance of its employees.